Pengaruh Variasi Bentuk Geometris Bata Beton Interlock Tipe Segitiga dan Lego terhadap Kekuatan Tekan - Radinda, Aura Azafilia; Sutriono, Bantot; Trimurtiningrum, Retno (CV. Information Technology Training Center - Indonesia (ITTC), 2025)
This The demand for efficient and environmentally friendly building materials has driven the development of interlocking concrete blocks with various geometric shapes. This study aims to analyze the effect of geometric shape variations of interlocking concrete blocks Triangle and Lego types on compressive strength, using the Cube block as a control sample. The tests were conducted on samples measuring 5×5×5 cm. The results indicate that block geometry significantly affects stress distribution and failure patterns. Based on the test results, the Cube block (control) achieved the highest compressive strength of 66.69 Kg/cm², followed by the Lego block with 51.68 Kg/cm² Grade II, and the Triangle block with 47.26 Kg/cm² Grade III according to SNI 03-0349-1989 for concrete masonry units. These differences in compressive strength demonstrate that the more complex and taller the block geometry, the greater the stress concentration that reduces strength performance. The Cube block showed the most uniform load distribution, the Lego block exhibited moderate strength due to its interlocking system that enhances stability, while the Triangle block had the lowest strength due to its narrower load-bearing area. Therefore, a compact and well-proportioned geometric design, such as the Lego type interlock, proves to be more structurally efficient than the taller triangular form.